Pemodelan Analisis Gap dan Kebijakan Green IT: Systematic Literature Review Menggunakan PRISMA - Wicaksono, Soetam Rizky; Setiawan, Rudy; Purnomo (Jurnal Pekommas, 2023)
Green IT Management, which aims to save energy in the business process ecosystem, is rarely used in the field of information technology. Because there is still little research and empirically, the application of Green IT is still in the modeling framework or local policies set stage, so not all companies are willing and able to do it. Because there is a gap between theory development and theory implementation, the right research direction is required so that the Green IT policy can be updated with the most recent conditions and accurately adopted. As a result of this situation, research questions must be addressed, such as whether the research gap from Green IT from its inception to 2022 exists, and whether the current Green IT policy modeling research direction can lead to implementation research. Using the PRISMA method as a guideline for conducting systematic literature reviews on the 200 most cited articles in the Scopus database, Google Scholar, and Semantic Scholar. In the final stage, 20 articles with conceptual discussions, 12 articles with empirical research, and 10 articles with policy implementation discussions were discovered. Based on the findings of the SLR study, it is possible to conclude that the first, the research gap, remains in the implementation section. Next, modeling and policy have not resulted in comprehensive implementation. Green IT research is still in its early stages, despite its steady progression over the last ten years. Empirically, not all companies are willing or able to implement because experimental research is still relatively limited in comparison to policy modeling research. According to this explanation, there is a gap between the implementation and development of theories or policy frameworks within the context of Green IT.